Investigation of the improving effect of raw and charred hawthorn on functional dyspepsia based on interstitial cells of Cajal - Ai, Li; Zhang, Lilin; Liang, Qi; Tian, Yao; Chen, Tao; Wu, Chunjie (Frontiers in Sustainable Food Systems, 2022)
Background Raw hawthorn (RH) is a traditional Chinese medicine commonly used to treat indigestion. Charred hawthorn (CH) is obtained from RH by charring. It is reported that the effect of CH treatment on dyspepsia is stronger than RH. However, this has not been fully proven. The purpose of this study was to compare the effects of RH and CH on functional dyspepsia (FD) model rats. And contribute to the development of dietary therapy for dyspepsia. Methods SPF-grade male SD rats were divided into 5 groups: the control group, the model group, the Mos group, the RH group, and the CH group. The FD rat model was established by using the methods of water restriction, fasting, tilting cage restraint, day and night upside down, swimming, and tail damping. The body weight of rats in each group was recorded. And the gastric emptying rate, intestinal propulsive rate, and the levels of motilin (MTL), gastrin (GAS), and 5-HT in serum were compared in each group. The expression of C-kit in the stomach and small intestine of each group was compared by immunofluorescence and PCR. Results RH and CH could increase weight, improve the gastric emptying rate and intestinal propulsive rate, and promote the secretion of motilin (MTL), gastrin (GAS), and 5-HT in the serum of FD rats. RH and CH can upregulate the expression of the characteristic protein c-kit of ICC in the stomach and small intestine of FD model rats, and the effect of CH is stronger than RH. Conclusion RH and CH may increase the number of interstitial cells of Cajal (ICC) in the gastrointestinal tract by upregulating c-kit expression, thus improving gastrointestinal motility in FD model rats. And compared with RH, CH has certain advantages.